The graphical representation of clothing store location and its application with potential method / Khairunnisha Amira Johar ... [et al.]. - Johar, Khairunnisha Amira; Mohd Amin, Mohammad Adam Hafiz Nor; Tuah, Muhammad Fared; Mamat, Siti Salwana (Faculty of Administrative Science and Policy Studies, 2025)
Multi-criteria Decision Making (MCDM) is a widely utilized approach for addressing decision problems by assessing pairwise comparisons of alternatives. MCDM involves evaluating various elements as input and deriving weighted outcomes for each alternative. The Analytic Hierarchy Process (AHP) and Potential Method (PM) are two examples of tools within MCDM. The PM employs a directed graph known as a preference, generated through paired comparisons, to establish a value function for the set of alternatives. In this study, PM is applied to the store location selection problem, with AHP already providing results. The objective is to demonstrate the use of PM in decision-making. The obtained results are then compared, revealing similar rankings for alternatives between the two methods. Consequently, PM is deemed comparable to AHP in effectively addressing real-life problems with multiple criteria.